In praise of P2P. (Economist, 2004)
The article examines peer-to-peer (P2P) file-sharing networks, a global information-storage system. The technology, used by millions to download songs, is reviled by the entertainment industry. In America and Europe, music and film companies are lobbying for new laws to outlaw P2P technology. Yet rather than being demonised, there are good reasons why the technology should be celebrated--and its benefits more widely studied and exploited. The equation of P2P with piracy has obscured the fact that the same technology is also being constructively applied in all sorts of fields, from content distribution and internet-routed phone calls to distributed storage and search. Peer-to-peer technology is emerging as a powerful new approach to building large-scale computer systems. Peer-to-peer connects computers directly--and once enjoined, personal computers can do things they are unable to do alone. Most P2P systems let users pool resources, be it processing power, storage capacity or bandwidth. The danger is that efforts to stamp out P2P's illegal uses might also blight the prospects for its virtuous uses, by hindering investment.